The Learning Preferences of Generation Z in Active Learning and Its Implications for Improving Educational Quality: A Perspective of Educational Management - Arda Yunita Subardi; Rugaiyah; Supadi (Jurnal Ragam Pengabdian, 2026)
The changing characteristics of 21st-century students, particularly Generation Z, drive the need for transformation in learning approaches. This generation demonstrates a strong preference for active learning models that require engagement, technology, and contextual learning experiences. This study aims to examine how Gen Z's preference for active learning can serve as a strategy for improving educational quality from the perspective of educational management. The method used is a literature review with a qualitative descriptive approach. The findings indicate that the systematic implementation of active learning, supported by adaptive educational management, can enhance learning outcomes, student satisfaction, and teaching effectiveness. Managerial implications include flexible curriculum planning, faculty training in active pedagogy, and a quality assurance system based on participatory learning.